Nilai Pendidikan Karakter dan Perilaku Tokoh dalam Kumpulan Cerpen Ketika Mas Gagah Pergi dan Kembali karya Helvy Tiana Rosadan Implikasinya terhadap Pembelajaran Sastra - Sadikin, Ali (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2024)
The Value of Character Education and Character Behavior in a Collection of Short Stories When Mas Gagah Goes and Returns by Helvy Tiana Rosa and Its Implications for Literature Learning. The objectives of this study are 1) To determine the value of character education in a collection of short stories When Mas Gagah Goes and Returns by Helvy Tiana Rosa and its implications for Literature Learning. 2) to determine the behavior of the characters in the short stories collection When Mas Gagah Goes and Returns by Helvy Tiana Rosa and its implications for literary learning 3) to determine the relationship between character education and the short story When Mas Gagah Goes and Returns by Helvy Tiana Rosa and its implications for literary learning. The method in this study uses a qualitative method because it does not use numbers. The author only prioritizes appreciation of the interaction or concept being studied. The theory used is the theory of Samani and Hariyanto. This study used descriptive qualitative method. The data of this research were obtained from a collection of short stories in the novel. The analysis in this study is the value of character education and character behavior. 1) The values ​​of character education include (1) religious values, (2) honesty, (3) tolerance, (4) discipline, (5) hard work, (6) creative, (7) independence, (8) desire know, (9) Like to read, (10) Responsibility, (11) Social Spirit (Friendly, respectful, environmental care, and social care), (12) National spirit. 2) character behavior includes (1) religious values, (2) honesty, (3) tolerance, (4) discipline, (5) hard work, (6) creative, (7) independence, (8) curiosity, ( 9) Love to read, (10) Responsibility, (11) Social Spirit (Friendly, respectful, environmental care, and social care), (12) National spirit.